Method Sharh Al-Hadith Sheikh Al-Nawawi in His Book; Tanqih Al-Qawl Al-Hath Ith Fi Sharh Lubab Al-Hadith - Abdurrohman, Abdurrohman; Nurkomala, Siti; Guilin, Xie; Jiao, Deng (Journal International Dakwah and Communication, 2021)
The study of hadith after that experienced a stagnation of almost a century and a half. However, along with the times, gradually the study of hadith gained attention again in the last half of the 19th century, until the beginning of the 20th century, with the inclusion of hadith studies in the curriculum of pesantren-pesantren and madrasah. In this century one of the scholars of Idonesian hadith, Shaykh Nawawi al-Bantani, wrote the book of Tanqih al-Qawul al-Hadith fi Shar? Lubab al-Hadith, this book which later became a reference in several Traditional Islamic Boarding Schools that implemented the yellow book recitation system in the archipelago. In addition, it is also used as material for book studies in the recitation of books in certain mosques. However, in-depth study of this book is still lacking, including the study of the sharah method used. Based on this fact, the author in this paper discusses the Methodology of the Nawawi al-Bantani Hadith Syarh in the Book of Tanqih al-Qawul al-Hadith fi Sharh Lubab al-Hadith.  The Book of Tanqi? al-Qawul al-Hathith is an explanatory or sharah of the previous scholarly hadith book Lubab al-Hadith written by Imam al-Suyuti. The Book of Tanqi? al-Qawul al-Hathith contains approximately 40 chapters of hadith related to various religious studies in the form of akidah, shari'a, muamalah. From the reading of each chapter consists of 10 hadiths. As for the systematics of the book of Tanq?? al-Qawul al-Hathith, it can be inferred through its dominance, namely globally or using the ijm?l? method